2020
DOI: 10.1029/2020gc009388
|View full text |Cite
|
Sign up to set email alerts
|

Electrokinetic Contributions to Self‐Potential Signals From Magmatic Stressing

Abstract: Volcanic unrest is often accompanied by anomalous geophysical and geochemical signals that are generally attributed to processes within the subvolcanic plumbing system (Salvage et al., 2017). Precise eruption forecasting remains a key issue in volcanology and depends on the correlation of volcanic precursors to subsurface causative mechanisms (Magee et al., 2018; Sparks, 2003). A major challenge in volcano monitoring is to establish whether a period of volcanic unrest will culminate in an eruption or wane with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 83 publications
(140 reference statements)
1
7
0
Order By: Relevance
“…However, it has been shown that a two-way coupling approach is more applicable for temporally protracted perturbations (Neuzil, 2003;Rutqvist et al, 2002), where subsurface strain affects hydraulic rock properties (e.g., κ, ϕ) which in turn govern the flow behaviour and in turn stresses and strains. Similar to studies by e.g., Hutnak et al (2009); Cur- Neither of our simulations account for the temperature dependence of parameters such as permeability (Ikard & Revil, 2014), fluid properties (Arens et al, 2020) or elastic parameters (Head et al, 2021), all of which have an effect on geophysical anomalies modelled in our study; a dedicated analysis is required to assess this influence. Although we neglect thermoelectric processes caused by strong thermal gradients (Corwin & Hoover, 1979;Fitterman & Corwin, 1982) in the HTU simulations, we find that for a maximum temperature change of 0.18 • C (unrest III) at the plateau, the thermoelectric potential (TEP) is ± 0.3 mV and 0.1 mV using a thermoelectric coupling coefficient of ± 1.5 mV/ • C and ± 0.5 mV/ • C (Revil & Mahardika, 2013;Ikard & Revil, 2014), respectively.…”
Section: Model Limitationsmentioning
confidence: 64%
See 4 more Smart Citations
“…However, it has been shown that a two-way coupling approach is more applicable for temporally protracted perturbations (Neuzil, 2003;Rutqvist et al, 2002), where subsurface strain affects hydraulic rock properties (e.g., κ, ϕ) which in turn govern the flow behaviour and in turn stresses and strains. Similar to studies by e.g., Hutnak et al (2009); Cur- Neither of our simulations account for the temperature dependence of parameters such as permeability (Ikard & Revil, 2014), fluid properties (Arens et al, 2020) or elastic parameters (Head et al, 2021), all of which have an effect on geophysical anomalies modelled in our study; a dedicated analysis is required to assess this influence. Although we neglect thermoelectric processes caused by strong thermal gradients (Corwin & Hoover, 1979;Fitterman & Corwin, 1982) in the HTU simulations, we find that for a maximum temperature change of 0.18 • C (unrest III) at the plateau, the thermoelectric potential (TEP) is ± 0.3 mV and 0.1 mV using a thermoelectric coupling coefficient of ± 1.5 mV/ • C and ± 0.5 mV/ • C (Revil & Mahardika, 2013;Ikard & Revil, 2014), respectively.…”
Section: Model Limitationsmentioning
confidence: 64%
“…Neither of our simulations account for the temperature dependence of parameters such as permeability (Ikard & Revil, 2014), fluid properties (Arens et al., 2020) or elastic parameters (Head et al., 2021), all of which have an effect on geophysical anomalies modeled in our study; a dedicated analysis is required to assess this influence. Although we neglect thermoelectric processes caused by strong thermal gradients (Corwin & Hoover, 1979; Fitterman & Corwin, 1982) in the HTU simulations, we find that for a maximum temperature change of 0.18°C (unrest III) at the plateau, the thermoelectric potential (TEP) is ±0.3 and 0.1 mV using a thermoelectric coupling coefficient of ±1.5 mV/°C and ±0.5 mV/°C (Ikard & Revil, 2014; Revil & Mahardika, 2013), respectively.…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations